Application of a discrete approach to designing the transport component of municipal solid waste logistics - E. E. Vitvitsky; E. S. Galaktionova; N. I. Yuryeva (Вестник СибАДИ)
Introduction. The growth of the urban area has led to the need to transfer landfills for the disposal of solid municipal (household) waste (MSW) to more remote locations on new sites. Representations and approaches to cargo transportation planning are an essential factor, separate planning of individual applications does not allow determining the results of future work with sufficient accuracy, since such an approach does not allow taking into account the interaction of rolling stock from different routes with each other and loading machines. The purpose of the study is to design the transportation of MSW in regional communications based on a discrete approach and theoretical provisions of operational planning of road freight transportation.Materials and methods. Within the framework of the conducted research, a normative approach was applied to the planning of freight transportation costs and descriptive models for describing the functioning of road transport systems of regional road freight transportation.Results and discussion. The solution of tasks related to the design of cargo transportation, including in regional communications, is due to the need in advance, prior to experience, knowledge of the results of future activities, since it is impossible to accumulate the work of road transport and then fix it. The results of cargo transportation depend on many factors, including the availability of a design methodology that allows you to adequately reflect the processes of their implementation. The use of mathematical modeling made it possible to reliably build plans for the transportation of MSW and determine the cost of their implementation.Conclusion. It has been revealed that possible downtime of both road trains and excavators is the reason for not fulfilling the operational transportation plan defined by separate planning. The use of the same rolling stock for customers with different transportation distances in the region will be accompanied by different costs.